ANALISIS KESULITAN BELAJAR BAHASA ARAB SISWA SMP IX PERGURUAN ISLAM MODERN AMANAH 1 - Aditia Saputra; M. Halim Lukman Rasyid; Muhammad Abdul Yunus (Fakultas Agama Islam Universitas Tjut Nyak Dhien, 2023)
Arabic is the language of the Qur'an and Hadith which is the source of Islamic law so without understanding it we will find it difficult to understand and understand the content of the Qur'an and Hadith, therefore one of the government policies under the auspices of the ministry of religion, Arabic is a compulsory subject that must be studied in Islamic educational institutions from exposure to Madrasah Ibtidaiyah to Islamic College. The type of research that the author used in this study is research field (field research), where this research is carried out to obtain data from concrete problems in the field in the form of sentence form information that gives an idea, attitude, and enthusiasm when participating in learning. The main source of data was obtained by making direct observations in the field, namely teachers and students of Modern Islamic School Amanah 1. The results of interviews of several students regarding the affective aspect (realm of taste) in Arabic learning can be interpreted as few of them have the ability to learn Arabic because some of them have low motivation in learning Arabic and most of them will learn when the next day there are assignments or daily tests or when told by their parents to research results, Data analysis and discussion about the analysis of the difficulty of learning Arabic at SMP 1 Amanah Medan can be concluded that the factors for students having difficulty learning Arabic include the lack of interest and motivation from within students to learn Arabic, the difficulty of reading and understanding the meaning of each Arabic vocabulary and the teacher's driving method that is too monotonous.